2011
DOI: 10.1111/j.1872-034x.2011.00912.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatobiliary membrane transporters in primary biliary cirrhosis

Abstract: The secretion of bile normally depends on the function of a number of membrane transport systems in hepatocytes and cholangiocytes. The transport of solutes from the blood to the bile is driven by transport systems in the plasma membrane of the basolateral and canalicular surfaces of the hepatocytes. In cholestatic animal models, the expression of hepatobiliary transporters changes in response to functional impairment of the efflux of bile salts and various organic anions. In recent years, several studies have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 65 publications
(72 reference statements)
1
6
0
Order By: Relevance
“…191 MRP1 and OST α/β, which are not expressed or expressed at low levels in normal hepatocytes, are upregulated in patients with PBC. 149,190,193,194 Consistent with the literature findings, data from our laboratory indicated that MRP1 protein was expressed in liver tissue from a patient with PBC (Figure 1). Interestingly, our findings suggest that MRP1 was expressed primarily in the inflamed tissues in macrophages around the hepatocytes in PBC.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…191 MRP1 and OST α/β, which are not expressed or expressed at low levels in normal hepatocytes, are upregulated in patients with PBC. 149,190,193,194 Consistent with the literature findings, data from our laboratory indicated that MRP1 protein was expressed in liver tissue from a patient with PBC (Figure 1). Interestingly, our findings suggest that MRP1 was expressed primarily in the inflamed tissues in macrophages around the hepatocytes in PBC.…”
Section: Introductionsupporting
confidence: 89%
“…189 Interestingly, it was reported that these alterations may be related to the adaptation of transporters, and that expression patterns may change from early to late stage PBC. 190,193 In addition to the changes in expression, the localization of MRP2 was altered in PBC stage III. 191 MRP1 and OST α/β, which are not expressed or expressed at low levels in normal hepatocytes, are upregulated in patients with PBC.…”
Section: Introductionmentioning
confidence: 99%
“…Bile acids play an important role in regulating the metabolism balance of lipids in vivo (1). They are converted from cholesterol in liver by a series of enzymes, and they maintain a dynamic balance through the uptake and efflux of hepatocellular transporter as well as the enterohepatic circulation (2). Some liver diseases and drug-induced liver injury are often accompanied by obstacles in the synthesis, metabolism and excretion of bile acids, potentially leading to the accumulation of bile acids.…”
Section: Introductionmentioning
confidence: 99%
“…PBC causes functional impairment of bile salt and organic anion efflux. In response, hepatobiliary transporters are expressed to prevent bile acid accumulation in hepatocytes . We previously described that the lack of adaptation to the upregulation of hepatobiliary transporters may be related to PBC progression …”
Section: Introductionmentioning
confidence: 99%
“…In response, hepatobiliary transporters are expressed to prevent bile acid accumulation in hepatocytes. 1 We previously described that the lack of adaptation to the upregulation of hepatobiliary transporters may be related to PBC progression. 2,3 The organic anion transporter peptide 1B3 (OATP1B3; also called OATP8 or solute carrier organic anion transporter family member 1B3 [SLCO1B3]), which is expressed in the basolateral membrane of hepatocytes, is especially important for the transport of agents such as gadolinium-ethoxybenzyl-diethylenetriamine pentaacetic acid (Gd-EOB-DTPA), as well as the uptake of endogenous substances and xenobiotics into the hepatocytes.…”
Section: Introductionmentioning
confidence: 99%